High-performance ambipolar benzodifurandione-based donor-acceptor copolymer with balanced hole and electron mobility. (March 2019) - Cheng, Sun; Yu, Seong Hoon; Kwon, Soon-Ki; Chung, Dae Sung; Kim, Yun-Hi
Abstract: Well-balanced ambipolar benzodifurandione (BDO) donor–acceptor copolymers were synthesized by tuning its intramolecular charge transfer nature by expanding the volumetric portion of the donor moiety, i.e., by using thiophene copolymerized with thiophene vinylene thiophene (TVT) or selenophene vinylene selenophene (SVS). Photophysical analyses revealed that BDO-SVS formed highly aggregated states in the solution state compared with BDO-TVT, facilitating a well-ordered self-assembled crystalline structure in the solid state. Using two-dimensional grazing incident X-ray diffraction and quantitative pole figure analyses, we established that the molecular orientation and degree of crystallinity was higher in BDO-SVS than in BDO-TVT. The morphological features identified by atomic force microscopy also showed a higher crystalline nature of SVS derivative, implying that SVS can strengthen intermolecular charge transport. This improved environment for charge transport, was revealed by the performance of organic field-effect transistors: BDO-SVS had superior performance than that of BDO-TVT for both hole and electron mobilities. This research shows that BDO, with a strong acceptor moiety, renders high-performance ambipolar characteristics when copolymerized with an expanded and aggregating donor moiety, such as SVS. Highlights: New benzodifurandione-based donor-acceptor copolymers. Well balanced ambipolar benzodifurandione. BDO-SVS had superior performance than that of BDO-TVT for OTFT.